Actual and Perceived Knowledge About COVID-19: The Role of Information Behavior in Media - Granderath, Julia S.; Sondermann, Christina; Martin, Andreas; Merkt, Martin (Frontiers in Psychology, 2021)
The COVID-19 pandemic poses a health threat that has dominated media coverage. However, not much is known about individual media use to acquire knowledge about COVID-19. To address this open research question, this study investigated how perceived threat is linked to media use, and how media use is associated with perceived and actual knowledge about COVID-19. In a German online survey conducted between April 16 and April 27, 2020, N=952 participants provided information on their perceived threat and media use to inform themselves about COVID-19. In this process, they indicated how well they are informed about COVID-19 (perceived knowledge) and subsequently completed a COVID-19 knowledge test (actual knowledge). Results indicated that individuals who felt more threatened by COVID-19 used media more often to inform themselves (b = 0.20, p < .001) but focused on fewer different media channels (b = 0.01, p < .001). Further, frequent media use was associated with higher perceived knowledge (b = 0.47, p < .001), but not with higher actual knowledge about COVID-19 (b = - 0.01, p = .938), reflecting an illusion of knowledge. Additionally, using fewer media channels was linked to higher perceived (b = 2.21, p < .001) and actual knowledge (b = 2.08, p = .008). Finally, explorative analyses on the use of different media channels revealed that an illusion of knowledge emerged for using social media, public television, and newspapers. Potential explanations for the findings and implications for future research are discussed.